Breeding biology of domesticated Eurasian Collared Dove (Columbidae) Streptopelia decaocto Frivaldszky 1838 in Saidpur, Bangladesh - Kabir, M Ashraful (International Journal of Environment, 2014)
Two pairs of domesticated Eurasian Collared Dove Streptopelia decaocto reared at eighteen months for its breeding performance in intensive system. One pair was homozygous albino al//al x al//al and another pair was one wild type +//al and another albino al//al. Another experimented four pairs of doves were produced from these two pairs. Out of six pairs total 114 squabs were produced during the research period. Total three albino pairs produced 100% albino squab and different coloured male and female produced different colours which were 50% each. Sex ratio of male and female were observed 1:1. Experimental doves were reared in cages measures 23x20x16 and 25x22x18 inches and feed were supplied all day long with wheat, corn, mustard, broken rice and burnt soil. Intake feed were 15 gram per dove in a day. During the time of this observation only hypervitaminosis and worm infestations were observed and the mortality rate was few. Only in one pair (rosy ? x wild type ?) produced 11 male (46%) and 13 female (54%) out of 24 squabs; this was slightly exceptional. In total 114 squabs from six pairs only one rosy male and pied rosy female were found. Breeding record of this research suggests that the colour patterns are first wild type then rosy and finally albino gradually.DOI: http://dx.doi.org/10.3126/ije.v3i2.10571 International Journal of the Environment Vol.3(2) 2014: 48-54